2021
DOI: 10.3390/mi12111433
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pH and Thermal Analysis of Paper-Based Microchip Electrophoresis

Abstract: Paper-based microchip electrophoresis has the potential to bring laboratory electrophoresis tests to the point of need. However, high electric potential and current values induce pH and temperature shifts, which may affect biomolecule electrophoretic mobility thus decrease test reproducibility and accuracy of paper-based microfluidic electrophoresis. We have previously developed a microchip electrophoresis system, HemeChip, which has the capability of providing low-cost, rapid, reproducible, and accurate point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…As a result, the pH in the right reservoir is significantly higher than in the microchannel, reaching as high as 11.34. The pH difference between the anode and cathode is about 1.34, which is consistent with the pH shifts observed in a microchip electrophoresis experiment (Hasan et al 2021). The EK model disregards reactions; hence the fluctuation of ion concentration within the EOF system cannot be accurately depicted.…”
Section: Influence Of Electrode Reactions On Ions Concentration and Phsupporting
confidence: 87%
“…As a result, the pH in the right reservoir is significantly higher than in the microchannel, reaching as high as 11.34. The pH difference between the anode and cathode is about 1.34, which is consistent with the pH shifts observed in a microchip electrophoresis experiment (Hasan et al 2021). The EK model disregards reactions; hence the fluctuation of ion concentration within the EOF system cannot be accurately depicted.…”
Section: Influence Of Electrode Reactions On Ions Concentration and Phsupporting
confidence: 87%
“…For instance, devices made with inexpensive paper or fabric materials could reduce the cost and complexity of device assembly, facilitating their adoption by users lacking the requisite experience or resources for microfabrication. Paper-based MCE systems have already been developed for the analysis of other types of biomolecules (Hasan et al, 2021). Both droplet-based and inertial microfluidics have shown promise for integration with ion-mobility spectrometry (IM-MS), a gas-phase and label-free MS technique that outperforms traditional liquid-phase methods in separation ability and isomer Multichannel microfluidic lectin barcode platform.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The fundamental principle behind Gazelle TM is hemoglobin electrophoresis in which different hemoglobin variants can be separated based on mobility differences under an electric field (Figure 1D). Gazelle has been tested in clinical studies in four different countries with more than 700 subjects and demonstrated a capability of identifying major Hb variants, including HbA, HbE, HbS, and HbF, in adults as well as in newborns with SCD, sickle cell trait, hemoglobin C disorder, and hemoglobin E disorder [28,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%